Caracterização geofísica no Gabro Santa Catarina, São Sepé (RS) - Moreira, César Augusto [UNESP]; Pereira, Alice Marques [UNESP]; Cavalheiro, Mara Lia Dias (My University, 2014)
Geophysical methods are widely used in mineral exploration for several types of mineral deposits. When combined with direct studies as geochemistry, a substantial increase in the probability of ore discovery is possible in mineral exploration activities. Electrical geophysical methods are particularly promising in studies related to the search of sulphides due to the contrast of physical properties electric resistivity and chargeability. This paper presents the results obtained from the application of Resistivity (DC) and Induced Polarization methods, through the electrical profiling technique, aiming at evaluating the potential mineral of a gabbro intruded in a metasedimentary sequence, in an area where several occurrences of gold and copper were described. This gabbro is ranked on the Basic-Ultrabasic stratiform bodies, which gather peridotites, gabbros, and layered anortosites. Three radial lines of electrical profiling were performed, spaced of 60° and crossing at the area center, with readings of electric resistivity and chargeability in Wenner-Schlumberger array. The association of low resistivity and high chargeability areas has allowed defining potentially mineralized zones related to structures that condition the drainage net in the gabbro domain. Grains of gold detected through geochemical prospection of alluvial sediments dowstream from the gabbro may have originated from leaching of ores deposited in fractures through the action of river waters within the gabbro domain, possibly consisting of sulphides and gold.

Os métodos geofísicos são largamente empregados na pesquisa dos mais diversos tipos de depó- sitos minerais. Quando combinados com estudos diretos como geoquímica em amostras de solos ou rochas, possibilitam um aumento substancial na probabilidade de descoberta de jazimentos. Os métodos geofísicos elétricos são particularmente promissores em estudos voltados à busca de sulfetos devido ao contraste das propriedades físicas resistividade elétrica e cargabilidade. Este trabalho apresenta os resultados da aplica- ção dos métodos eletrorresistividade e polarização induzida, por meio da técnica de caminhamento elétrico, com o objetivo de avaliar o potencial mineral do gabro Santa Catarina, localizado no município de São Sepé (RS), numa região onde foram descritas várias ocorrências de ouro e sulfetos. Este gabro é classificado no domínio de Corpos Básico-Ultrabásicos Estratiformes, que reúne peridotitos, gabros e anortositos acamadados. Foram realizadas três linhas de caminhamento elétrico dispostas de forma radial, com cruzamento no centro da área e separação de 60° entre linhas e leituras de resistividade elétrica e cargabilidade em arranjo Wenner- -Schlumberger. A associação de áreas de baixa resistividade e alta cargabilidade obtida a partir de modelos de inversão bidimensionais permitiu definir zonas potencialmente mineralizadas, relacionadas com estruturas que condicionam a rede de drenagem no domínio do gabro. Pintas de ouro detectadas em campanha de prospecção geoquímica em sedimento de corrente à jusante do gabro podem ser originadas da lixiviação de depósitos contidos em fraturas, por ação de águas fluviais no domínio do gabro, possivelmente caracterizados por sulfetos e ouro associado.
Geophysical characterization of the Santa Catarina Gabbro, São Sepé (RS)
Keywords: Gabbro Santa Catarina; Mineral research; Geophysics; Sulfides; Gold; Geochemistry; Gabro Santa Catarina; Pesquisa mineral; Geofísica; Sulfeto; Ouro; Geoquímica